Auto-antibodies against type I IFNs in > 10% of critically ill COVID-19 patients: a prospective multicentre study - Romain Arrestier; Paul Bastard; Thibaut Belmondo; Guillaume Voiriot; Tomas Urbina; Charles-Edouard Luyt; Adrian Gervais; Lucy Bizien; Lauriane Segaux; Mariem Ben Ahmed; Raphaël Bellaïche; Taï Pham; et al. (Annals of Intensive Care, 2022)
Abstract Background Auto-antibodies (auto-Abs) neutralizing type I interferons (IFN) have been found in about 15% of critical cases COVID-19 pneumonia and less than 1% of mild or asymptomatic cases. Determining whether auto-Abs influence presentation and outcome of critically ill COVID-19 patients could lead to specific therapeutic interventions. Our objectives were to compare the severity at admission and the mortality of patients hospitalized for critical COVID-19 in ICU with versus without auto-Abs. Results We conducted a prospective multicentre cohort study including patients admitted in 11 intensive care units (ICUs) from Great Paris area hospitals with proven SARS-CoV-2 infection and acute respiratory failure. 925 critically ill COVID-19 patients were included. Auto-Abs neutralizing type I IFN-α2, β and/or ω were found in 96 patients (10.3%). Demographics and comorbidities did not differ between patients with versus without auto-Abs. At ICU admission, Auto-Abs positive patients required a higher FiO2 (100% (70–100) vs. 90% (60–100), p = 0.01), but were not different in other characteristics. Mortality at day 28 was not different between patients with and without auto-Abs (18.7 vs. 23.7%, p = 0.279). In multivariable analysis, 28-day mortality was associated with age (adjusted odds ratio (aOR) = 1.06 [1.04–1.08], p < 0.001), SOFA score (aOR = 1.18 [1.12–1.23], p < 0.001) and immunosuppression (aOR = 1.82 [1.1–3.0], p = 0.02), but not with the presence of auto-Abs (aOR = 0.69 [0.38–1.26], p = 0.23). Conclusions In ICU patients, auto-Abs against type I IFNs were found in at least 10% of patients with critical COVID-19 pneumonia. They were not associated with day 28 mortality.